2001
DOI: 10.1111/1467-985x.00209
|View full text |Cite
|
Sign up to set email alerts
|

Dropping Out of University: A Statistical Analysis of the Probability of Withdrawal for UK University Students

Abstract: From individual level data for an entire cohort of undergraduate students in the`old' universities in the UK, we use a binomial probit model to estimate the probability that an individual will`drop out' of university before the completion of their degree course. We examine the cohort of students enrolling full time for a 3-or 4-year degree in the academic year 1989±1990. We ®nd evidence to support both the hypothesis that the completion of courses by students is in¯uenced by the extent of prior academic prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
3
16

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 10 publications
5
149
3
16
Order By: Relevance
“…Students who do not live in Padova have higher attendance costs, and time constraints, since they have to spend more time travelling and, for resident students, performing domestic tasks, and this means that the time thus spent is not available for study (Dolton, Marcenaro, and Navarro 2003). For these reasons, students living in Padova are expected to be advantaged, but this does not necessarily mean more successful careers than other students, who may be more motivated to perform better and may be more integrated with their peer groups and the student community (Smith and Naylor 2001).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who do not live in Padova have higher attendance costs, and time constraints, since they have to spend more time travelling and, for resident students, performing domestic tasks, and this means that the time thus spent is not available for study (Dolton, Marcenaro, and Navarro 2003). For these reasons, students living in Padova are expected to be advantaged, but this does not necessarily mean more successful careers than other students, who may be more motivated to perform better and may be more integrated with their peer groups and the student community (Smith and Naylor 2001).…”
Section: Covariatesmentioning
confidence: 99%
“…For these reasons, many studies have been carried out in several countries which analyse students' outcomes during university (see, e.g., McCall 1999, 2002;Smith and Naylor 2001;Montmarquette, Mahseredjian, and Houle 2001;Arulampalam, Naylor, and Smith 2004;Scott and Kennedy 2005;Bradley and Lenton 2007;Lassibille and Gomez 2009;Arias Ortiz and Dehon 2011). However, the temporal dimension has not always been considered, and when it is, it is not taken into account in a discrete framework, which is clearly needed in many educational inquiries, since the assumption of continuous time models -that the precise time of occurrence of an event is known -may be unrealistic in educational contexts (Singer and Willett 1993;Scott and Kennedy 2005;Arias Ortiz and Dehon 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent statistical analysis of the probability of withdrawal for UK university students indicated that non-completion was more probable for students from low-ranked occupationally defined social classes (Smith & Naylor, 2001). Many assume that this is a matter of academic failure.…”
Section: Class and Drop-out In The Ukmentioning
confidence: 99%
“…Smith & Naylor, 2001;Cingano & Cipollone, 2007;Stratton, O'Toole, & Wetzel, 2008;. Si è così in presenza (cfr.…”
Section: Figura 1 -Laureati Al T 2 T 3 E T 4 Per Ateneo (%) Figurunclassified